Tema dan Nilai Moral dalam Cerita Anak Bergambar Dwibahasa "Hore! Adat Barikan Wayahe Teka" Karya Andi Sep Kurniawan - Inno Tyas; Putri Nurul Azizah (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Children's fiction stories as part of children's literature not only function as entertainment but also as teaching. Themes and moral values ​​cannot be separated and have an important role in the presentation of children's fiction stories. This research aims to determine the themes and moral values ​​in bilingual children's fiction stories Hore! Adat Barikan Wayahe Teka custom by Andi Sep Kurniawan. This type of research uses qualitative descriptive research with Burhan Nurgiyantoro's moral values ​​research design. The data from this research are words, phrases and sentences that have potential for data analysis. The data source in this research was obtained from bilingual illustrated children's story books Hore! Adat Barikan Wayahe Teka. Data collection techniques with documentation. Next, the data analysis technique uses the Miles and Huberman model. The results and discussion in the research describe the themes that are the basis for the development of illustrated children's stories. Themes that appear in fictional stories with bilingual titles Hore! Adat Barikan Wayahe Teka customs are in the form of Barikan customs and traditions. Meanwhile, there are four moral values ​​found that relate to humans' relationship with God, including praying to God and being grateful. Humans' relationship with themselves includes a high level of curiosity. Human relationships with each other include the pleasure of helping and mutual cooperation. The relationship between humans and the natural environment, namely preserving nature and preserving customs. So the conclusion from the research data above is that children's fiction stories contain themes of customs and traditions, as well as teaching moral values ​​to readers, especially children. So it is useful in learning moral values ​​for children today as readers of literary story.